Structural design of Abutment Using GEO 5 Program - Husen, Abdurahman Yasin, Anto Budi Listyawan,S.T,M.Sc, Yenny Nurchasanah, S.T., M.T (2015)
The soil mechanics and designing technique got the revolution quickly in the 2000's, especially in Indonesia which has many types of soil. By the developing technology era of construction building, it is also in the geotechnical technology. To make easy in the designing of foundation, especially; abutment, the using of software is also needed. Based on the problem above, the writer want to investigate the usage of program in designing the abutment, the program is Geo5. In this designing, the data is taken from Pagotan Bridge Rehabilitation, Pacitan. Central Java. The abutment with concrete as the structure, controlling the stability of sliding, overturning, soil weight volume (ɤ) 1,424 gr/cm3; cohesion (c) 0 kN/cm2; friction angle (φ) 30o.The geology condition of soil layer in the field is sand; the high of abutment is 5.8 m. The calculation method is done twice; manual calculation and Geo5 program calculation. After the calculation, the result show that the stability manual factor of sliding is 2.04>2 (safety), stability of overturning 3.07>2 (safety). The differences result between manual calculation and Geo5 program is because the calculation of lateral earth pressure is difference. The manual calculation used Rankine while Geo5 program used modification Rankine, it is Mazindrani.